Insights into the pathogenesis of cerebral fusiform aneurysms: high-resolution MRI and computational analysis. (25th February 2021) - Sabotin, Ryan Phillip; Varon, Alberto; Roa, Jorge A; Raghuram, Ashrita; Ishii, Daizo; Nino, Marco; Galloy, Adam E; Patel, Devanshee; Raghavan, Madhavan L; Hasan, David; Samaniego, Edgar A
Abstract : Background: Intracranial fusiform aneurysms are complex and poorly characterized vascular lesions. High-resolution magnetic resonance imaging (HR-MRI) and computational morphological analysis may be used to characterize cerebral fusiform aneurysms. Objective: To use advanced imaging and computational analysis to understand the unique pathophysiology, and determine possible underlying mechanisms of instability of cerebral fusiform aneurysms. Methods: Patients with unruptured intracranial aneurysms prospectively underwent imaging with 3T HR-MRI at diagnosis. Aneurysmal wall enhancement was objectively quantified using signal intensity after normalization of the contrast ratio (CR) with the pituitary stalk. Enhancement between saccular and fusiform aneurysms was compared, as well as enhancement characteristics of fusiform aneurysms. The presence of microhemorrhages in fusiform aneurysms was determined with quantitative susceptibility mapping (QSM). Three distinct types of fusiform aneurysms were analyzed with computational fluid dynamics (CFD) and finite element analysis (FEA). Results: A total of 130 patients with 160 aneurysms underwent HR-MRI. 136 aneurysms were saccular and 24 were fusiform. Fusiform aneurysms had a significantly higher CR and diameter than saccular aneurysms. Enhancing fusiform aneurysms exhibited more enhancement of reference vessels than non-enhancing fusiform aneurysms. Ten fusiform aneurysms underwent QSM analysis, and five aneurysms showed microhemorrhages. Microhemorrhage-positive aneurysms had a larger volume, diameter, and greater enhancement than aneurysms without microhemorrhage. Three types of fusiform aneurysms exhibited different CFD and FEA patterns. Conclusion: Fusiform aneurysms exhibited more contrast enhancement than saccular aneurysms. Enhancing fusiform aneurysms had larger volume and diameter, more enhancement of reference vessels, and more often exhibited microhemorrhage than non-enhancing aneurysms. CFD and FEA suggest that various pathophysiological processes determine the formation and growth of fusiform aneurysms.